2016
DOI: 10.1111/isj.12123
|View full text |Cite
|
Sign up to set email alerts
|

Issues that support the creation of ICT workarounds: towards a theoretical understanding of feral information systems

Abstract: enterprise system (ES) software is often supplemented independently by end users who develop personal solutions that establish connections between the required business practices and the ES. One solution is a type of information and communications technology workaround, a feral information system (FIS) – defined as a workaround designed to achieve certain requirements by using any information technology tool that an end user uses in conjunction with, or instead of, the mandated information system. To explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
1
28
0
1
Order By: Relevance
“…Strong and Volkoff (2010), Beijsterveld and Groenendaal (2016), and van den Hooff and Hafkamp (2017) linked workarounds to functionality misfits (both deficiencies and impositions). We also found earlier theories about organization-enterprise system misalignment (Soh & Sia, 2004) and several other studies, such as Spierings, Kerr, and Houghton (2017) and Gasser (1986), that described workarounds as resulting from a misfit between systems and work practices without referring to the theory of organization-enterprise system fit or similar theories. While most of these studies described workarounds that individuals or groups of individuals devise, Beijsterveld and Groenendaal (2016) described workarounds as a solution for companies when they cannot affordably or practically change.…”
Section: Theorizing Workaroundssupporting
confidence: 68%
See 2 more Smart Citations
“…Strong and Volkoff (2010), Beijsterveld and Groenendaal (2016), and van den Hooff and Hafkamp (2017) linked workarounds to functionality misfits (both deficiencies and impositions). We also found earlier theories about organization-enterprise system misalignment (Soh & Sia, 2004) and several other studies, such as Spierings, Kerr, and Houghton (2017) and Gasser (1986), that described workarounds as resulting from a misfit between systems and work practices without referring to the theory of organization-enterprise system fit or similar theories. While most of these studies described workarounds that individuals or groups of individuals devise, Beijsterveld and Groenendaal (2016) described workarounds as a solution for companies when they cannot affordably or practically change.…”
Section: Theorizing Workaroundssupporting
confidence: 68%
“…Journal Workarounds result from organization-system misfit (Gasser, 1986;Soh & Sia, 2004;Safadi & Faraj, 2010;Strong & Volkoff, 2010;Beijsterveld & Groenendaal, 2016;van den Hooff & Hafkamp, 2017;Li et al, 2017;Spierings et al, 2017) 8…”
Section: Interviews Observations Documentsunclassified
See 1 more Smart Citation
“…[5] _ "Where a mismatch occurs between the expectations of technology and actual working practice, employees may implement a 'workaround' by deviating from set procedures". [13] Notwithstanding certain contradictory points of view expressed in [77], it can be concluded that the terms of shadow IT, feral systems and IT workaround refer to the same phenomenon, i.e. IT that is not controlled by IT department.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We can see similar accommodating practices across the information systems literature, albeit not necessarily under the same names. For example, workarounds have been very much influential and authors have written quite extensively around them (e.g., Choudrie et al 2016;Seethamraju 2015;Spierings et al 2017). Rejection, similarly, has appeared in the literature, in different forms, e.g., discontinuance (Cao et al 2019) and Soliman et al (Soliman and Rinta-Kahila 2019) provide a thorough review of the different forms and conceptualizations this may take.…”
Section: The Timeliness Of Our Findingsmentioning
confidence: 99%